Vital Roux, Forgotten Forerunner of Modern Business Games. (February 2015) - Touzet, Léo; Corbeil, Pierre
Aim. This article presents thepioneering work of Vital Roux, a French businessman and author who proposed, in the1800s, a teaching method to train business people which closely resembles theexperiential method central totoday's business games . Background. This presentation indirectly discusses the fundamental issue ofbusiness games' success as an educational innovation. We recall briefly thatthe roots of business games aredistant, multiple, and far-ranging. Method. Thepedagogy advocated by Vital Roux is revealed andinnovative aspects of his educational system are noted and discussed.Roux's obscurity is underlined, and a plausibleexplanation for the relative failure of his project is proposed. A social and historicalhypothesis is then suggestedto explain the success which business games have won in theUnited States a century and a half later. Conclusion. Roux's key thoughts are summarized, suggesting he can appear as aforgotten forerunner ofmodern business games .